A sala de aula de estágio curricular supervisionado: um estudo no contexto da formação inicial de professores de língua inglesa - Ligia Cristina Domingos Araujo (2019)
The present work had the objective to carry out a study in an English Teaching Practicum I classroom of a Language Teaching Program in a Southeast Brazilian university. Through the theoretical-methodological approach of ethnography in the classroom, I sought to understand how this particular space was constructed through the relationships developed among its participants. Thus, I observed an English Teaching Supervised Practicum I classroom during the second semester of 2017. I identified, described and analyzed events and interactional processes that produced patterns of interaction between the teacher and her students. These patterns constituted the frames of reference through which the subjects created repertoires of behavior and interaction(GREEN; DIXON, 1994). The analysis of the observed patterns showed that the Supervised Practicum I classroom was a place where people with different desires and ways of interpreting reality met and, therefore, it was also place of disagreements. Teachers and students experiences, times, and desires were often not convergent. Such divergences were sources of conflict and, for that reason, the understanding of this space considered the "perceptual mismatches" (KUMARAVADIVELU, 2003) among the members of that group. Based on this, I proposed three types of mismatches as structuring elements for the analysis: mismatches of experiences, of times and of desires. The reflections on the disagreements indicate that the relations built within that environment and the events that occurred were influenced by internal (intertextual) and external (intercontextual) factors and actors in the classroom(GREEN; CASTANHEIRA, 2012). In addition, the teacher condition and student resistance were also important elements to understand the collective production of that classroom. Disagreements, teacher mental health issues and resistance were the characteristic patterns of the class studied and were limiting factors to students' learning opportunities in the course.